Nanomechanical properties of biochemically modified dentin bonded interfaces - Santos, Paulo Henrique dos [UNESP]; Karol, S.; Bedran-Russo, A. K. B. (Wiley-Blackwell, 2011)
P>The effect of biomodification of dentin matrices using collagen cross-linkers, glutaraldehyde (GD) and grape seed extract (GSE), on the reduced modulus of elasticity (Er) and nanohardness (H) of the hybrid layer and underlying dentin was investigated at the dentin-resin bonded interface. The coronal dentin of nine molars were exposed and divided into groups: 5% GD, 6 center dot 5% GSE and control. Control samples were etched, bonded with Adper Single Bond Plus and Premise composite. GD and GSE were applied for 1 h prior to bonding procedures. After 24 h, samples were sectioned, and resin-dentin beams were either kept in distilled water or exposed to collagenase treatment for 24 h. Nano-indentations were performed at the hybrid layer and underlying dentin. GD and GSE treatment increased the Er and H of resin-dentin interface structures when compared to the control group (P < 0 center dot 05), particularly the hybrid layer, and may be a promising novel approach to strengthen the dentin-resin bonded interface structures when using these adhesive system and resin-based composite.
Keywords: collagen; adhesion; mechanical properties; interfaces; dental materials